KARAKTERISTIK ALTERASI BAWAH PERMUKAAN PADA SUMUR CKK-1A KEDALAMAN 250-822 METER WILAYAH KERJA PANAS BUMI DAERAH X, KABUPATEN SUKABUMI, JAWA BARAT - Jasin Arrasyid Nugraha; Karyono; Oman Abdurahman; Adang Saputra; Lano Adhitya; Mochamad Nur Hadi; Wanda Adinugraha (PPSDM Geominerba, 2022)
This research was conducted at the CKK-1A geothermal exploration well from a depth of 250 – 822 meters which is located in the geothermal working area area X, Sukabumi Regency, West Java. This study aims to determine the lithology type, alteration mineral type, alteration mineral zone, alteration type, temperature, fluid type, and correlate measured temperature (logging temperature and drilling mud temperature) with alteration mineral temperature (geothermometer). Megascopic observations were carried out using a loupe with a magnification of 20x, while microscopic analysis and XRD (X-Ray diffraction) analysis were carried out by the PSDMBP laboratory. There are 5 types of lithological variations in the research wells, namely, altered tuff breccia, altered andesitic breccia, altered andsit, altered tuff, and altered volcanic breccia. From the results of microscopic analysis and XRD analysis, several types of alteration minerals were present, namely chlorite, zeolite, carbonate, secondary quartz, tridymite, albite, clay, oxide, and pyrite. Based on the assemblage of alteration minerals present, there are 2 zones of alteration minerals, namely: 1) Chlorite – Zeolite Zone from a depth of 250 – 732.40 meters, 742.25 – 803.60, and 805.25 – 822 meters; and 2) Clay Mineral Zone from a depth of 732.40 – 742.25 meters and 803.60 – 805.25 meters. The Chlorite – Zeolite Zone is interpreted as a Sub Propylitic Alteration Type with a temperature range of >200°C and formed in neutral fluids, then the Clay Mineral Zone is interpreted as an Argillic Alteration Type with a temperature range of <180°C and formed in near neutral acidic fluids. The correlation between measured temperature (logging temperature and drilling mud temperature) and hydrothermal alteration mineral temperature (mineral geothermometer) shows that there is a mismatch between the presence of high temperature minerals >200°C, with measured temperature values ​​only ranging from 10°C – 58°C . As well as the absence of increased heat present in Mud Temperature Out. It is interpreted that the high temperature characteristic minerals have cooled and become fossilized. This can also be seen from the presence of low temperature clay minerals (monmorillonite) in the high temperature chlorite - zeolite zone.